Modeling a multidimensional model of memory performance in obsessive-compulsive disorder: A multilevel meta-analytic review - Persson, Sofia; Yates, Alan; Kessler, Klaus; Harkin, Ben (Journal of abnormal psychology (1965), 2021)
Even though memory performance is a commonly researched aspect of obsessive-compulsive disorder (OCD), a coherent and unified explanation of the role of specific cognitive factors has remained elusive. To address this, the present meta-analysis examined the predictive validity of Harkin and Kessler's (2011b) executive function, binding complexity, and memory load (EBL) Classification System concerning affected versus unaffected memory performance in OCD. We employed a multilevel meta-analytic approach (Viechtbauer, 2010) to accommodate the interdependent nature of the EBL model and interdependency of effect sizes (305 effect sizes from 144 studies, including 4,424 OCD patients). Results revealed that the EBL model predicted memory performance; that is, as EBL demand increases, those with OCD performed progressively worse on memory tasks. Executive function was the driving mechanism behind the EBL's impact on OCD memory performance, as it negated binding complexity, memory load, and visual or verbal task differences. Comparisons of subtask effect sizes were also generally in accord with the cognitive parameters of the EBL taxonomy. We conclude that standardized coding of tasks along individual cognitive dimensions and multilevel meta-analyses provides a new approach to examine multidimensional models of memory and cognitive performance in OCD and other disorders. (PsycInfo Database Record (c) 2021 APA, all rights reserved).